“[eɪ], [oʊ], [aɪ]”: A Quantitative Study on High School Students’ Errors in Pronouncing English Diphthong - Kurniasy, Dessy; Idami, Zahratul; Keumala, Meta; Husna, Nina Hayatul (Universitas Teuku Umar, 2023)
The objective of this study was to find out the errors made by students in pronouncing diphthong “eɪ, oʊ, aɪ”. This study used a quantitative approach. To obtain valid data, the researchers administered a test that was carried out to 30 students as the sample taken from IX IPA 1 of SMA Negeri 4 Langsa. Based on the research, the data showed that one student made errors 6 times and got score 50, three students made errors 5 times and got score 58. Seven students made errors 4 times and got score 67, four students made errors 3 times and got score 75. Eight students made errors 2 times and got score 83. Six students made errors 1 time and got score 92. There was only one student who made no errors and got score 100. The cause of errors in pronouncing English diphthongs was revealed to be affected by interference of the mother tongue which is popular as the basic principle of contrastive analysis. The coming pre-service teachers were able to devise appropriate lesson plan in diphthong pronunciation teaching. In addition, it is also hoped that they can construct the suitable material for various levels and needs of learners.